2021
DOI: 10.1115/1.4051728
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Deformation of Copper Nanoparticle Based Joints and Bonds

Abstract: The inelastic deformation properties of sintered metal nanoparticle joints are complicated by the inherent nanocrystalline and nanoporous structures as well as by dislocation networks formed in sintering or under cyclic loading. Creep rates of sintered nanocopper structures were found to be dominated by the diffusion of individual atoms or vacancies, while dislocation motion remained negligible up to stresses far above those of practical interest. Rapid sintering of one material led to unstable structures the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The propensity to voiding becomes even more worrisome in today’s 2.5/3D fine pitch assemblies in the packaging industry, that are a result of a solder-joint volume shrinkage by a factor of 1000 or more. This size-reduction significantly impacts the joints’ reliability by generating issues such as early electromigration failures, transformation of the entire solder joint to a complete intermetallic joint, and enhancement of the sporadic Kirkendall voiding. , Our recent work confirmed much higher voiding propensity at scales typical of 2.5/3D miniaturized assemblies and revealed important differences in systematic trends in comparison with larger joints. , To address the latter problem, researchers have explored a variety of alternative techniques for solder-free interconnection such as direct Cu–Cu bonding and sintering of metal nanoparticles or nanostructured Cu onto copper pillars. , In the earlier stages of these studies, Cu nanoparticulate pastes had been shown to form joints after sintering at relatively low temperatures. …”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…The propensity to voiding becomes even more worrisome in today’s 2.5/3D fine pitch assemblies in the packaging industry, that are a result of a solder-joint volume shrinkage by a factor of 1000 or more. This size-reduction significantly impacts the joints’ reliability by generating issues such as early electromigration failures, transformation of the entire solder joint to a complete intermetallic joint, and enhancement of the sporadic Kirkendall voiding. , Our recent work confirmed much higher voiding propensity at scales typical of 2.5/3D miniaturized assemblies and revealed important differences in systematic trends in comparison with larger joints. , To address the latter problem, researchers have explored a variety of alternative techniques for solder-free interconnection such as direct Cu–Cu bonding and sintering of metal nanoparticles or nanostructured Cu onto copper pillars. , In the earlier stages of these studies, Cu nanoparticulate pastes had been shown to form joints after sintering at relatively low temperatures. …”
Section: Introductionmentioning
confidence: 56%
“…As seen in Figure , the sintered joints feature porosity due to the evaporation and partial evacuation of organic binding material during sintering, that leads to inferior mechanical properties. Overall, said binders are used in the pastes to hold together the otherwise non-self-supported nanoparticles, yet not allowing them to agglomerate below the sintering temperature of 300 °C. ,, …”
Section: New Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…10–13 Further investigations have shown that np-Cu holds a significant advantage as a joint precursor over nano-Cu paste, mostly due to the latter's tendency to form oxides and incorporate non-conductive bonding chemicals during the sintering process. 9,14…”
Section: Introductionmentioning
confidence: 99%